THE EFFECT OF PERFORMANCE MEASUREMENT ASPECTS ON PDAM MAKASSAR CITY COMPETITIVENESS - Rifkhi Anugrah Husain; Rahman Pura (Jurnal Ilmiah METHONOMI, 2021)
The purpose of this research is to examine the effect of measuring the performance of PDAM Makassar City on competitiveness in terms of financial and non-financial performance using the Balanced Scorecard approach through four perspectives: financial, customer, internal business, and growth and learning. This research uses a quantitative approach and is a type of explanatory research. The sample used in this study was 20 employees and 20 customers of PDAM Makassar City. To test the hypothesis, multiple linear analysis was tested using SPSS version 22.00. The results of this study indicate that there is a significant positive relationship between the Balanced Scorecard on the competitiveness of PDAM Makassar City.